Operative management and outcomes in patients with myxomas: A single-center experience - Alhasso, Ahmed Abdulfattah; Ahmed, Okba F.; Mohammed-Saeed, Dana H.; Kakamad, Fahmi H.; Almodhaffer, Saif S.; Zaid, Zaid A.; Abdullah, Hiwa O.; Ali, Razhan K.; Kakamad, Suhaib H.; Omar, Diyar A.; Abdalla, Berun A.; Mohammed, Shvan H.; et al. (Frontiers in Surgery, 2023)
Background Cardiac myxoma is a rare cardiac tumor that may be asymptomatic or can cause embolization or intracardiac obstruction, leading to heart failure, sudden cardiac death, and arrhythmia. This study aims to report an 11-year experience of a single center in the management of cardiac myxoma. Method This study is a single-center retrospective case series. Eighty cases of cardiac myxoma were collected in Ibn Albitar's specialized center for cardiac surgery. Transthoracic echocardiography was used to make the preoperative diagnosis in all patients. The surgeries were undertaken through the standard approach of a median sternotomy. All four cardiac chambers were thoroughly explored for additional myxomas. The major objective of the operations was complete tumor resection. Result The mean age of the patients was 46.3 years. Females (67.5%) were predominant over males (32.5%). Shortness of breath was the most common symptom (86.25%). The left atrium was the most affected site (83.75%), followed by the right atrium (13.75%). Coronary artery bypass grafting was required as the secondary or associated intervention in 19 (23.75%) cases. The recurrence rate was 11.25%, with a mortality rate of 3.75%. Conclusion Recurrence and tumor embolism are risks of surgical intervention for myxoma. Good preparation using transthoracic echocardiography as a diagnostic tool and standard median sternotomy to complete resection of the tumors can decrease the rate of recurrence, embolism, and even mortality.